云南省人力资源开发与经济社会发展研究 = Research on the human resource and economic developmet in Yunnan - 杨雯 Yang, Wen (2008)
Based on the data of the fifth census in China, 2000, the thesis analyzes the present situations and problems of human resource in Yunnan Province. Qualitative and quantitative analysis are used as principal method in this thesis.